Latest results on searches for dark matter signatures in galactic and extragalactic selected targets by the MAGIC Telescopes. Issue 4 (May 2016) - Giammaria, P; Aleksić, J; Lombardi, S; Maggio, C; Palacio, J; Rico, J; Vanzo, G; Vazquez Acosta, M
Abstract: Discovering the nature of Dark Matter (DM) is one of the fundamental challenges of the modern physics. Indirect searches of DM are devoted to look for non-gravitational signals of its presence in the highly DM dominated cosmic regions. Within the weakly interacting massive particles (WIMPs) scenario, we expect very high energy (VHE) gamma-ray emissions resulting from annihilation and/or decay of DM particles. Since the beginning of operations, the Major Atmospheric Gamma Imaging Cherenkov (MAGIC) telescopes are carrying out deep observations of several promising DM targets, with the aim of detecting such signals or alternatively setting stringent constrains to DM particle models in the TeV mass region. In this contribution we present the latest indirect DM search results achieved by MAGIC on several targets, such as dwarf satellites – where MAGIC reached the strongest constraints on DM annihilation searches above few hundreds of GeV –, galaxy clusters, and the Galactic Center.